The Nephroprotective Effect of Andrographis Paniculata Ethanol Extract Chitosan Nanoparticles on Vero cells - Wahyu Kurniawan Dhadhang; Nabilah; Nuryanti; Novrial Dody; Aries Nurulita Nunuk (E3S Web of Conferences)
Nephroprotective agents are substances that protect the kidneys from nephrotoxicity. Some nephroprotective agents are derived from medicinal plants. Sambiloto (Andrographis paniculata) is one of the herbal plants known to have a nephroprotective effect. This study aims to determine the nephroprotective potential of chitosan-based ethanol extract nanoparticles of Andrographis paniculata on the Vero cell line. Andrographis paniculata ethanol extract nanoparticles were prepared using ionic gelation. These nanoparticles exhibited a viability percentage ranging from 97.251% to 107.258% at concentrations of 50-1000 ppm. In the acute protective test, Andrographis paniculata ethanol extract nanoparticles at a chitosan-based concentration of 500 ppm showed a protective ability of 3.26%. In the recovery test, they exhibited a recovery ability ranging from 4.35% to 21.01% at concentrations of 100-500 ppm, and in the chronic protection test, the recovery ability ranged from 5.01% to 14.24% at concentrations of 100-500 ppm. Chitosan-based ethanol extract nanoparticles of Andrographis paniculata are non-toxic and have nephroprotective abilities in both recovery and protection tests.